The Use of Wizer.me As A Media to Stimulate Students’ Motivation in Writing Descriptive Text in SMA Swasta HKBP Doloksanggul - Maria A. Simanjuntak; Anggun Rezeki Manurung; Nurhayati Sitorus; Marnala Pangaribuan (UNIVERSITAS PGRI YOGYAKARTA, 2025)
AbstractThis study aims to know that wizer.me as a media can stimulate students' motivation in writing descriptive text. There is phenomena in this research, Some students stated that they still had difficulties when they were writing texts. They said that they had difficulties in grammar, content, vocabulary, mechanics etc. it makes students will lose interest and become bored during the learning process. To achieve the objectives of this study, the writer uses a qualitative descriptive text. The source of the data came from student’s tenth grade in SMA Swasta HKBP Doloksanggul. The instrument of data collection used was phone (Iphone Version), stationaries, worksheet, and technique of data collection used writing test and interview. To analyze the data, four steps were used namely: data collection, data condensation, data display, and the last conclusion drawing. Research result show that the students’ ability increases in writing descriptive text, this can be seen from the students' writing after using wizer.me in some aspects, such as: Correlation in content relates to each in writing descriptive text, good coherence of organization in writing descriptive text, improving the grammar in writing descriptive text, improving the vocabulary in writing descriptive text, good spelling and punctuation of mechanic in writing descriptive text, increasing the students’ motivation in writing descriptive text, increasing the students willingness in writing and making the class more peaceful. It can be concluded that’s wizer.me can stimulate students’ motivation in writing descriptive text. This means that students feel that wizer.me is one of the media that easy to use and can make them interested in learning English in writing class.Keywords: Wizer.me, Writing Descriptive Text, Students’ Motivation